Comparison of efficacy and safety between palonosetron and ondansetron to prevent postoperative nausea and vomiting in patients undergoing non-laparoscopic surgery: A systematic review and meta-analysis of randomised controlled trials - Babu Lal; Ragavi Alagarsamy; Jitendra Kumar; Anshul J. Rai; Vineeta Yadav; Rajnish Joshi; Md. Yunus (Indian Journal of Anaesthesia)
Background and Aims: Postoperative nausea and vomiting (PONV) is a common and distressing complication in all types of surgeries involving general anaesthesia. To establish evidence for best clinical practices, this meta-analysis compares the efficacy and safety of palonosetron and ondansetron in preventing PONV in patients undergoing non-laparoscopic surgeries. Methods: A PRISMA-guided systematic review and meta-analysis was conducted in PubMed, Google Scholar, Semantic Scholar, and Cochrane Library to identify comparative studies that reported the efficacy (nausea and vomiting) at postoperative time points, namely T1 (0–2 hours), T2 (0–6 hours), T3 (12–24 hours), T4 (24–48 hours), and T5 (24–72 hours), as well as safety (number of incidence of adverse effects). A meta-analysis of the efficacy and safety groups was performed using a random-effects model. Results: Nineteen randomised controlled trials were included. Pooled risk ratio (RR) revealed that patients receiving palonosetron were significantly less likely to develop nausea [0–2 h, RR = 0.82 (95% confidence interval (CI): 0.50, 1.34), P = 0.317, I2 = 15.3%], [0–6 h, RR = 0.76 (95% CI: 0.44, 1.29), P = 0.137, I2 = 45.7%], [12–24 h, RR = 0.39 (95%CI: 0.16, 0.96), P = 0.088, I2 = 54.2%], [24–48 h, RR = 0.44 (95% CI: 0.20, 0.96), P = 0.598, I2 = 0%], [24–72 h, RR 0.22 (95% CI: 0.08, 0.57), P = 0.119, I2 = 53.0%] and vomiting [0–2 h, RR = 0.59 (95% CI: 0.29, 1.23), P = 0.868, I2 = 0%], [0–6 h, RR = 1.42 (95% CI: 0.74, 2.72), P = 0.790, I2 = 0%], [12–24 h, RR = 0.14 (95% CI: 0.04, 0.51), P = 0.749, I2 = 0.0%], [24–48 h, RR = 0.24 (95%CI: 0.09, 0.62), P = 0.561, I2 = 0%], [24–72 h, RR = 0.11 (95% CI: 0.02, 0.58), P = 0.859, I2 = 0%]. The safety profiles of palonosetron and ondansetron were comparable [headache: RR = 0.82 (95%CI: 0.65, 1.04), P = 0.940, I2 = 0%], [drowsiness: RR = 0.96 (95%CI: 0.54, 1.71), P = 0.870, I2 = 0%], [constipation: RR=1.20 (95%CI: 0.52, 2.79), P = 0.650, I2 = 0%], [dizziness: RR = 0.60 (95%CI: 0.44, 0.83), P = 0.644, I2 = 0%]. Conclusion: Palonosetron and ondansetron exhibited comparable efficacy in the early hours (0–6 h). Palonosetron showed superior efficacy beyond 6 hours, providing sustained PONV prophylaxis in patients undergoing various surgeries, excluding laparoscopic procedures.